Evidence-based guidelines for pediatric clinical trials: focus on StaR Child Health. Issue 5 (September 2012) - Sampson, Mario R; Benjamin, Daniel K; Cohen-Wolkowiez, Michael
Clinical trials in children are challenging and filled with important ethical considerations that differ from adults. Given difficulties associated with pediatric clinical trials, off-label prescribing is a common practice in pediatrics, which can lead to adverse safety events and efficacy failures. To overcome these consequences, in the past 15 years, legislation in the USA and Europe has provided incentives to industry and increased government funding to conduct pediatric trials. Pediatric trial networks have also been formed to decrease the knowledge gap. However, challenges to performing pediatric trials and lack of standardization and guidelines regarding studies in children still exist. Standards for Research (StaR) in Child Health, begun in 2009, aims to improve the design, conduct and reporting of pediatric trials. This organization uses a consensus guideline approach involving academic, government and industry stakeholders to identify and disseminate best practices for pediatric trials. Six out of 11 planned standards are currently published.